Hybrid plasmonic nano-emitters with controlled single quantum emitter positioning on the local excitation field - Dandan Ge (Nature Portfolio, 2020)
The authors study, on hybrid plasmonic nano-emitters, the spatial overlap between the exciting optical near-field and the nanoscale active medium whose position is controlled via surface plasmon-triggered two-photon polymerization. They also demonstrate such systems down to the single photon level.